2011
DOI: 10.1038/ejcn.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial to investigate the effects of acute consumption of a blackcurrant juice drink on markers of vascular reactivity and bioavailability of anthocyanins in human subjects

Abstract: Background/Objectives: To study the bioavailability of anthocyanins and the effects of a 20% blackcurrant juice drink on vascular reactivity, plasma antioxidant status and other cardiovascular disease risk markers. Subjects/Methods: The study was a randomised, cross-over, double-blind, placebo-controlled acute meal study. Twenty healthy volunteers (11 females and 9 males) were recruited, and all subjects completed the study. Fasted volunteers consumed a 20% blackcurrant juice drink (250 ml) or a control drink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…Anthocyanin aglycones are reported to have greater bioavailability glycosylated anthocyanins. Among the glycosylated anthocyanins with the same aglycone structure, varying the sugar moiety of the glycosides and the position of the same glycoside on the same anthocyanin rings affects bioavailability (Kamonpatana et al 2014;Jin et al 2011;Ichiyanagi et al 2006). The present study showed that fermentation of black carrot with either of L. plantarum or A. oryzae changed the composition of anthocyanins, such Triglyceride (mg/dL) 69.2 ± 7.4 a 58.8 ± 6.5 b 56.6 ± 6.8 b,c 52.3 ± 6.3 c 56.3 ± 7.2 à OVX-CON, OVX rats fed a high-fat diet (HFD) with 2 % dextrin; BC, OVX rats fed HFD with 2 % lyophilized water extracts of black carrot; BCAO, 2 % lyophilized water extract of black carrot fermented with Asperillus oryzae; BCLP, OVX rats fed HFD with 2 % lyophilized water extract of black carrot fermented with Lactobacillus plantarum; Sham-CON, Sham rats fed a high-fat diet (HFD) with 2 % dextrin Mean ± standard deviation (n = 10) à Significantly different from the OVX-CON by two-sampled t test at P \ 0.05 a,b Values in the same column with different superscripts were significantly different by Tukey's test at P \ 0.05…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin aglycones are reported to have greater bioavailability glycosylated anthocyanins. Among the glycosylated anthocyanins with the same aglycone structure, varying the sugar moiety of the glycosides and the position of the same glycoside on the same anthocyanin rings affects bioavailability (Kamonpatana et al 2014;Jin et al 2011;Ichiyanagi et al 2006). The present study showed that fermentation of black carrot with either of L. plantarum or A. oryzae changed the composition of anthocyanins, such Triglyceride (mg/dL) 69.2 ± 7.4 a 58.8 ± 6.5 b 56.6 ± 6.8 b,c 52.3 ± 6.3 c 56.3 ± 7.2 à OVX-CON, OVX rats fed a high-fat diet (HFD) with 2 % dextrin; BC, OVX rats fed HFD with 2 % lyophilized water extracts of black carrot; BCAO, 2 % lyophilized water extract of black carrot fermented with Asperillus oryzae; BCLP, OVX rats fed HFD with 2 % lyophilized water extract of black carrot fermented with Lactobacillus plantarum; Sham-CON, Sham rats fed a high-fat diet (HFD) with 2 % dextrin Mean ± standard deviation (n = 10) à Significantly different from the OVX-CON by two-sampled t test at P \ 0.05 a,b Values in the same column with different superscripts were significantly different by Tukey's test at P \ 0.05…”
Section: Discussionmentioning
confidence: 99%
“…In the correlation analysis, a moderate positive correlation was observed between FRAP and uric acid (r = 0.31, p = 0.03). Studies with other food sources rich in polyphenols have also found a correlation between uric acid concentrations and FRAP values (Fernández-Pachón, Villaño, Troncoso, & Garcia-Parrilla, 2005;Godycki-Cwirko et al, 2010;Jin, Alimbetov, George, Gordon, & Lovegrove, 2011), suggesting that antioxidant activity determined by FRAP assay can be partly explained by an increase in uric acid concentrations. Considering the maximum increase in FRAP and uric acid concentrations 1 h after juice consumption, it was noted that the FRAP values exceed the increase in uric acid, suggesting that other components such as phenolic compounds influence the serum antioxidant potential.…”
Section: In Vivo Antioxidant Activitymentioning
confidence: 92%
“…Furthermore, the intake of red grape juice rich in anthocyanin reduced the concentrations of oxidized LDL and the activity of NADPH oxidase in dialysis patients [63], and the inhibitory effects of fruits containing anthocyanins on atherosclerosis were reported in elderly men [64]. Recent studies, however, showed no effects of blackcurrant juice [65] and blood orange juice [66] on cardiovascular risk markers.…”
Section: Cvdmentioning
confidence: 95%